1981
DOI: 10.1159/000131640
|View full text |Cite
|
Sign up to set email alerts
|

Formation of chromosome-type aberrations at the first cleavage after MMS treatment in late spermatids of mice

Abstract: Male mice were treated with graded doses of methyl methanesulfonate (MMS) and mated with untreated female mice during the six to ten days after treatment. The nature of the primary lesions induced in late spermatids was investigated by analysing the types and rates of chromosome aberrations in the first cleavage metaphases. The chromosome aberrations recovered at the first cleavage were predominantly of the chromosome-type. Their frequency increased exponentially with increasing dose of MMS. The results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 4 publications
(5 reference statements)
1
7
0
Order By: Relevance
“…Our finding that treatment of post-meiotic male germ cells with an S-phase-dependent chemical resulted in the production of mostly chromosome-type aberrations at the first-cleavage metaphase was consistent with other male exposure studies (Tanaka et al 1981, Albanese 1982, Matsuda & Tobari 1988, Pacchierotti et al 1994. The molecular mechanism, however, is uncertain.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding that treatment of post-meiotic male germ cells with an S-phase-dependent chemical resulted in the production of mostly chromosome-type aberrations at the first-cleavage metaphase was consistent with other male exposure studies (Tanaka et al 1981, Albanese 1982, Matsuda & Tobari 1988, Pacchierotti et al 1994. The molecular mechanism, however, is uncertain.…”
Section: Discussionsupporting
confidence: 92%
“…An advantage of this system is that the relative contribution of each parent to the incidence of chromosome anomalies can be assessed independently because the paternal and maternal chromosomes remain separated until the metaphase plate of the first mitotic division (McGaughey & Chang 1969), and because the maternal chromosomes show a higher degree of condensation (Donahue 1972). The analysis of mouse zygotes by conventional cytogenetics has already been used to demonstrate the induction of aneuploidy after treatment of female germ cells (reviewed by Mailhes & Marchetti 1994), and the induction of structural aberrations after treatment of male germ cells with various alkylating agents (Tanaka et al 1981, Albanese 1982, Matsuda & Tobari 1988, Pacchierotti et al 1994, radiomimetics or irradiation . Consistent findings of the male exposure studies were: (1) post-meiotic effects were primarily observed; and (2) the majority of the aberrations were of the chromosome type, rather than chromatid type, even after treatment with S-phase-dependent chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…23). Since almost 100% of mouse oocytes fertilized in vivo are karyologically normal (27,28), it would appear that the ICSI procedure per se, independently of freezing or freeze-drying, has some adverse affect upon chromosome stability. For mouse ICSI, the sperm neck region is damaged (17) or heads are separated from tails (29) before injection into the oocytes, and it would appear that the resulting damage to the plasma membrane increases the chance of chromosome aberrations occurring in the resulting embryo.…”
Section: Discussionmentioning
confidence: 99%
“…(d) Data are deficient in recently recognized endpoints like CNVs. (e) Lastly, the database contains a number of qualitative and quantitative exceptions as follows: (i) dominant lethal mutations following acrylamide exposure and germ cell tandem repeat mutations following exposure to mainstream tobacco smoke occur in the absence of significant increases in bone marrow or blood MN [5,75]; (ii) four chemicals (1,1-dimethylhydrazine, beta-propiolactone, diethylnitrosoamine and dimethylnitrosoamine) were negative in the bone marrow MN assay, but were found to be positive in the spermatid MN assay [89]; and (iii) three agents, MMS, acrylamide, and ionizing radiation showed quantitatively greater clastogenicity in exposed sperm (detected as chromosomal aberrations in zygotes) than in bone marrow of mice [152][153][154][155][156].…”
Section: Do Genotoxicity and Mutagenicity Assays In Somatic Cells Prementioning
confidence: 99%